First Record Of Necrotic Enteritis Caused By Clostridium Perfringens In Chickens From Chattisgarh (India) (Applied Biological Research, 2014)
The outbreak of several devastating diseases is one of the major constraints causing economic loss  so discouraging poultry rearing in India. Intestinal diseases are an important concern for modern  poultry industry because of low productivity, increased mortality and the associated contamination  of poultry products with pathogenic bacteria and their toxins. Necrotic enteritis is one of the world´s  most common diseases which cause mortality up to 10-40% (McDevit et al., 2006). Necrotic  enteritis caused by Clostridium perfringens in chickens is a risk to public health through food chain  (Van Immerseel et al., 2004). Necrotic enteritis in chicken due to C. perfringens has not earlier been  reported from Chhattisgarh (India).
Keywords: RECORD; Necrotic